2023
DOI: 10.1371/journal.pone.0294250
|View full text |Cite
|
Sign up to set email alerts
|

Burden of elevated lipoprotein(a) among patients with atherosclerotic cardiovascular disease: Evidence from a systematic literature review and feasibility assessment of meta-analysis

Panagiotis Orfanos,
Ana Filipa Fonseca,
Xingdi Hu
et al.

Abstract: Background Elevated lipoprotein(a) [Lp(a)] level is an independent genetic risk factor that increases the risk of atherosclerotic cardiovascular disease (ASCVD) by 2–4 fold. We aimed to report the burden of clinically relevant elevated Lp(a) in secondary prevention ASCVD population as the evaluation of such evidence is lacking. Methods A systematic literature review (SLR) was conducted using Embase®, MEDLINE®, and MEDLINE® In-Process databases to identify studies reporting burden of elevated Lp(a) levels fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Interestingly, a large systematic review showed an approximately two-fold increase in the relative risk for ischemic stroke related to high Lp(a) concentrations [ 113 ]. Moreover, meta-analysis data suggest that high Lp(a) levels are associated with increased odds of cognitive impairment and disability related to stroke [ 114 ]. However, the impact of Lp(a) levels on peripheral artery disease (PAD) is less clear, with conflicting findings in the literature.…”
Section: The Role Of Lp(a) In Cardiovascular Disease: Focusing On Ath...mentioning
confidence: 99%
“…Interestingly, a large systematic review showed an approximately two-fold increase in the relative risk for ischemic stroke related to high Lp(a) concentrations [ 113 ]. Moreover, meta-analysis data suggest that high Lp(a) levels are associated with increased odds of cognitive impairment and disability related to stroke [ 114 ]. However, the impact of Lp(a) levels on peripheral artery disease (PAD) is less clear, with conflicting findings in the literature.…”
Section: The Role Of Lp(a) In Cardiovascular Disease: Focusing On Ath...mentioning
confidence: 99%
“…Elevated Lp(a) levels are identified as an independent genetic cardiovascular risk factor. It is estimated that individuals with elevated Lp(a) levels have a 2-4fold increased risk of ASCVD (atherosclerotic cardiovascular disease) [4]. A comprehensive meta-analysis www.journals.viamedica.pl/medical_research_journal indicates that one in five people worldwide has elevated Lp(a).…”
Section: Introductionmentioning
confidence: 99%